In Silico Analysis Identifies Intestinal Transit as a Key Determinant of Systemic Bile Acid Metabolism - Sips, Fianne L. P.; Eggink, Hannah M.; Hilbers, Peter A. J.; Soeters, Maarten R.; Groen, Albert K.; van Riel, Natal A. W. (Frontiers in Physiology, 2018)
Bile acids fulfil a variety of metabolic functions including regulation of glucose and lipid metabolism. Since changes of bile acid metabolism accompany obesity, Type 2 Diabetes Mellitus and bariatric surgery, there is great interest in their role in metabolic health. Here, we developed a mathematical model of systemic bile acid metabolism, and subsequently performed in silico analyses to gain quantitative insight into the factors determining plasma bile acid measurements. Intestinal transit was found to have a surprisingly central role in plasma bile acid appearance, as was evidenced by both the necessity of detailed intestinal transit functions for a physiological description of bile acid metabolism as well as the importance of the intestinal transit parameters in determining plasma measurements. The central role of intestinal transit is further highlighted by the dependency of the early phase of the dynamic response of plasma bile acids after a meal to intestinal propulsion.